2020
DOI: 10.2147/jpr.s241101
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electroacupuncture Treatment Attenuates Paclitaxel-Induced Neuropathic Pain in Rats via Inhibiting Spinal Glia and the TLR4/NF-κB Pathway</p>

Abstract: Background and Purpose: Neuropathic pain is a major side-effect of paclitaxel (PTX) chemotherapy. Although the precise mechanisms responsible for this pain are unclear, the activation of neuroglia and upregulation of the TLR4/NF-κB pathway are known to be involved. In this study, we determined whether electroacupuncture (EA) could limit mechanical hypersensitivity resulting from the chemotherapeutic drug PTX in rats, and investigated the potential mechanisms involved. Methods: Rats intraperitoneally received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 49 publications
0
25
1
1
Order By: Relevance
“…However, an earlier study by Zheng et al report no increment of spinal microglia activation associated with paclitaxel neuropathy using the same rat model as we used. In contrast, some recent studies reported obvious spinal microglia activation using the same paclitaxel model as we used in the present study [ 49 ]. Moreover, our recent study, which used the same paclitaxel model, also identified significant spinal microglia activation after paclitaxel treatment and we further evaluated the effect of electroacupuncture on alleviating microglia activation in spinal cord [ 11 ].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, an earlier study by Zheng et al report no increment of spinal microglia activation associated with paclitaxel neuropathy using the same rat model as we used. In contrast, some recent studies reported obvious spinal microglia activation using the same paclitaxel model as we used in the present study [ 49 ]. Moreover, our recent study, which used the same paclitaxel model, also identified significant spinal microglia activation after paclitaxel treatment and we further evaluated the effect of electroacupuncture on alleviating microglia activation in spinal cord [ 11 ].…”
Section: Discussioncontrasting
confidence: 85%
“…ERK1/2 signaling was recently found to be upregulated and contributed to PIPN by enhancing Nav1.7 expression in DRGs of a rat model of PIPN [ 74 ]. Besides, NF-κB signaling was shown to be upregulated in the spinal cord of a rat PIPN model [ 75 ]. These results suggest that lncRNAs may modulate mRNA expression involved in neurotrophin signaling pathway during PIPN, which may consequently affect downstream ERK1/2 s and NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an inhibitor of TLR4–NF‐κB signalling, pyrollidine dithiocarbamate, mitigated the spared nerve injury‐induced production of proinflammatory cytokines (Pei et al., 2018). Meanwhile, electroacupuncture attenuated paclitaxel‐induced mechanical allodynia, which was related to the inhibition of microglia and astrocytes in spinal cord, as well as the blockage of the TLR4–NF‐κB signalling pathway (Zhao et al., 2020). In the present study, TLR4–NF‐κB signalling activation by LPS significantly restored the mechanical allodynia, thermal hyperalgesia, apoptosis and the production of inflammation‐related factors reduced by Dex.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel significantly activates both microglia and astrocytes and increases the expression of inflammatory cytokines (IL-1 β and TNF- α ) in the lumbar spinal cord. EA treatment (10 Hz, 1 mA) at the bilateral ST36 point in rats suppressed the expression of inflammatory cytokines through the downregulation of the TLR4/NF- κ B pathway as well as suppressing activated microglia and astrocytes [ 71 ]. Besides TLR4, increased expression of TLR2 in the spinal cord and thalamus was also reportedly suppressed by EA in a CFA model [ 72 ].…”
Section: Central Sensitization In Pain Transmission and Modulationmentioning
confidence: 99%